Mechanism Of Action Of Vildagliptin And Its Role In Type 2 Diabetes Management (The Review of Diabetic Studies, 2024)
Background: Insulin resistance and lower production of insulin define a metabolic disorder called type 2 diabetes mellitus (T2DM). Appropriate management of blood glucose levels helps to reduce the risk of diabetes-related complications. Vildagliptin reduces dipeptidyl peptidase-4 (DPP-4) and is a viable new therapeutic choice. DPP-4 inhibitors help to sustain a constant blood sugar level by modulating the incretin system, which oversees either boosting or lowering glucagon levels depending on glucose synthesis. Unlike more traditional therapies like sulfonylureas, vildagliptin lowers blood sugar levels while also lessening the possibility of hypoglycemia and extra weight gain.Aim: This study intends to understand how vildagliptin works and what that implies for clinical practice so that type 2 diabetes might be better managed. This study investigates if vildagliptin is better than other antidiabetic drugs, how it affects glycemic indices, and how it increases incretin hormone action.Conclusion: Type 2 diabetes mellitus (T2DM) is a major health concern around the world due to its high treatment costs and rising incidence. Reducing related effects, especially microvascular disorders and cardiovascular ones, requires good glycemic management. An increasingly important class of antidiabetic medications, dipeptidyl peptidase-4 (DPP-4) inhibitors like vildagliptin are among the several treatment alternatives. Vildagliptin offers a variety of therapeutic benefits without a high risk of hypoglycemia or weight gain, depending on the incretin-enhancing method it employs—glucose-dependent insulin secretion, reduced glucagon release, or postprandial glucose management. In combination therapy with other antidiabetic medications, it provides a good balance and is well-tolerated, making it appropriate for a wide range of patients, including those with moderate to severe renal impairment. Vildagliptin treats multiple facets of diabetes thanks to its synergistic effects with insulin, sulfonylureas, metformin, and other medications. Vildagliptin's efficacy in protecting pancreatic beta-cell activity, improving overall medication adherence, and meeting glycemic objectives. Incorporating DPP-4 inhibitors into diabetes treatment improves clinical results and patient quality of life, as research highlights their wider therapeutic implications.